Oromotor dysfunction in minimally verbal children with cerebral palsy: characteristics and associated factors. Issue 6 (13th March 2022) - Mei, Cristina; Hodgson, Madeleine; Reilly, Sheena; Fern, Bethany; Reddihough, Dinah; Mensah, Fiona; Pennington, Lindsay; Losche, Annabel; Morgan, Angela
Abstract: Aim: To explore the characteristics and associated factors of oromotor dysfunction in minimally verbal children with cerebral palsy (CP) aged five to six years, recruited from a population-based registry. Methods: Twenty children with CP who were minimally verbal completed a standardised, observational oromotor assessment. Linear regression analyses examined the relationship between oromotor dysfunction and potential associated factors (e.g., fine and gross motor function, communication, and feeding). Results: Oromotor dysfunction affected every participant and was identified in all structures examined (i.e., face, jaw, lips, and tongue). Oromotor movements showed little dissociation among jaw, lip, and tongue movements. Oromotor dysfunction was univariately associated with the Manual Ability Classification System levels IV–V ( p = 0.001), reduced communication skills ( p = 0.002), and a prolonged eating duration (>45 min) ( p = 0.006), even when non-verbal cognition served as a covariate. Interpretation: Oromotor dysfunction was highly prevalent in our sample of minimally verbal children with CP, having significant functional impacts on feeding and communication. Findings suggest that fine motor function (i.e., Manual Ability Classification System levels IV–V) is a stronger predictor than gross motor function for identifying children with CP who are minimally verbal and at risk of oromotor dysfunction. IMPLICATIONS FOR REHABILITATION: Oromotor dysfunction was highly prevalent in our sample of minimally verbal children with cerebral palsy. Severe fine motor impairment strongly predicted oromotor dysfunction, indicating that fine motor function may provide an early indicator of impaired oromotor function for this clinical population. Robust, standardised measures of motor speech-related oromotor development suitable for children with cerebral palsy who are minimally verbal are lacking. Until such a measure is developed, formal evaluation may be achieved via oral motor assessments standardised for typically developing children, with the caveat one must interpret the results with caution.